A Commodity Production Model with Operational Flexibility of Investing Optional Capacity on Offshore Platforms - Civelek, Ismail (International Journal of Supply Chain Management, 2014)
We study the problem of operational flexibility on capacity investment of an oil producer. Our decision-maker operates only on land fields and has option to extend operations to offshore oil platforms. The operational flexibility arises from the ability to invest on offshore fields. Our main goal is to integrate offshore platforms from the chemical and petroleum engineering literature, and capacity investment from operations management literature. We use a mixed integer programming solution approach and set a basic model to analyse the value of operational flexibility. Our main contribution is to provide an operational flexibility option to the problem of oil drilling.